2021
DOI: 10.1039/d0dt04042h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular self-assembly of 1D infinite polyiodide helices in a phenanthrolinium salt

Abstract: Iodine atoms align into a 1D polymeric polyiodide chain, stabilized with the surrounding phenanthrolinium cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 82 publications
(88 reference statements)
1
16
0
Order By: Relevance
“…They are thought to enhance the mechanical performance and the thermal stability of polyiodides and, as recently shown, to modulate their conduction properties. I···I interactions, in addition to being an opportunity for semantic considerations, are the connectors that can make solid-state conduction feasible and efficient based on a Grotthuss-like mechanism, , which requires the preservation of orbital overlap along the iodine chains, a phenomenon favored by high iodine density. ,, Nonetheless, it has been shown that the physical properties, that is, electrical conductivity and thermal stability, of polyiodide chains are also affected by the supramolecular interactions they experience in the crystals . These details form a basis of information that can aid in the design of high-performance polyiodide-based solid-state conductors, which are of currently great practical interest for the development of new devices, especially for the preparation of solar cells , and batteries. , …”
Section: Introductionmentioning
confidence: 99%
“…They are thought to enhance the mechanical performance and the thermal stability of polyiodides and, as recently shown, to modulate their conduction properties. I···I interactions, in addition to being an opportunity for semantic considerations, are the connectors that can make solid-state conduction feasible and efficient based on a Grotthuss-like mechanism, , which requires the preservation of orbital overlap along the iodine chains, a phenomenon favored by high iodine density. ,, Nonetheless, it has been shown that the physical properties, that is, electrical conductivity and thermal stability, of polyiodide chains are also affected by the supramolecular interactions they experience in the crystals . These details form a basis of information that can aid in the design of high-performance polyiodide-based solid-state conductors, which are of currently great practical interest for the development of new devices, especially for the preparation of solar cells , and batteries. , …”
Section: Introductionmentioning
confidence: 99%
“…1,2 In most cases, polyiodides can be described with the general formula I 2m+n n− , in which n and m represent the number of iodide anions (I − ) and of iodine molecules (I 2 ), respectively. 3,4 In the solid state, polyiodides display a vast diversity of compositions and structures, ranging from the simplest and linear I 3 − and I 4 2− to the V-shaped I 5 − and zigzag I 23 3− anions, complex two-dimensional (2D) networks, and three-dimensional (3D) cage-like structures, such as I 9…”
Section: ■ Introductionmentioning
confidence: 99%
“…Though simple, this procedure can be varied in many ways depending on the solvent used and on the nature and size of the cation associated with the iodide or triiodide anion. 3 As a rule of thumb, large cations favor the formation of extended polyiodide chains in the solid state, 3,4,12 and various supramolecular interactions such as hydrogen or halogen bonds, 11,13−15 caging, 16,17 and anion•••π 18,19 concur to stabilize the chains within the crystalline material. 2 Polyiodides, though extensively studied, constitute a class of materials still relatively poorly understood, and their intrinsic structural unpredictability has prompted further research in this direction, 20 in particular, to rationalize the formation of polyiodide infinite chains, which are, in turn, sought for their potential applications as electrolytes in solar cells, 21−24 electrochemical devices, 25−27 and optical devices, 26,28 among others.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3,18,19 Recently, infinite PI chains stabilized with planar pyrroloperylene and phenantrolinium cations were reported. 20,21 In general, the stability of higher PIs decreases with the higher number of iodine atoms. In turn, larger PI units require bulky (soft) cations to stabilize them.…”
Section: ■ Introductionmentioning
confidence: 99%
“…PIs exhibit a great structural diversity in the crystalline state. Their discrete chains range from the minimal I 3 – unit up to I 29 3– . Besides, a number of I 2 ···I n m – adducts are reported in the Cambridge Structural Database (CSD) v.5.40 (Figure S1) which can be regarded as intermediate products of the addition reaction to form higher PIs. ,, Recently, infinite PI chains stabilized with planar pyrroloperylene and phenantrolinium cations were reported. , …”
Section: Introductionmentioning
confidence: 99%